Aportaciones a la etimología de algunos términos de origen prerromano (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The paper seeks to update some spanish words wich may have a clearer etymology in the light of recents advances in the field of Paleo-His- panic languages, and to bring out the contribution that Indoeuropean can pro- vide to the etymology of some terms usually labeled as “pre-Roman” in Etymological Dictionaries. Spanish terms such as sarna, roña, barro, charco, will be studied.
Keywords: Etymology; Pre-Roman Vocabulary; Indo-European; Pre-Roman Languages